Parents’ and children’s negotiations around health: the case of the HPV vaccine - Mcnaughton, Rebekah; Shucksmith, Janet; Spratt, Jenny; Philip, Kate; Flueckiger, Jennifer; Backett-Milburn, Kathryn (CRFR, 2010)
In 2007, the Scottish Government announced an in-school vaccination programme for teenage girls to protect against cervical cancer. In Scotland a young person under the age of 16 is deemed to have the legal capacity to consent to health care and treatment in certain circumstances. This raised a number of issues with schools and parents about the programme and choices around the vaccination decision. This briefing examines research findings that explored parents’ and young people’s understanding of these issues prior to the introduction of the new vaccine.
Keywords: Health Services; Parents and Parenting; Reproductive Issues; Young people